Ultrafast humidity sensor and transient humidity detections in high dynamic environments - Fang Liu; Jin Hong; Xiangdong Chen; Xing Ding; Shaopeng Li; Xiang Yu; Jiaqi Lu; Xuan Zhao; Kun Tang; Chenghua Xie; Kemei Zhao (Communications Engineering)
Abstract Limited by the adsorption and diffusion rate of water molecules, traditional humidity sensors, such as those based on polymer electrolytes, porous ceramics, and metal oxides, typically have long response times, which hinder their application in monitoring transient humidity changes. Here we present an ultrafast humidity sensor with a millisecond-level response. The sensor is prepared by assembling monolayer graphene oxide quantum dots on silica microspheres using a simple electrostatic self-assembly technique. Benefiting from the joint action of the micro spheres and the ultrathin humidity-sensitive film, it displays the fastest response time (2.76 ms) and recovery time (12.4 ms) among electronic humidity sensors. With the ultrafast response of the sensor, we revealed the correlation between humidity changes in speech airflow and speech activities, demonstrated the noise immunity of humidity speech activity detection, confirmed the humidity shock caused by explosions, realized ultrahigh frequency respiratory monitoring, and verified the effect of humidity-triggering in the non-invasive ventilator. This ultrafast humidity sensor has broad application prospects in monitoring transient humidity changes.